Neuroprotective role of nanoencapsulated quercetin in combating ischemia-reperfusion induced neuronal damage in young and aged rats. - Aparajita Ghosh; Sibani Sarkar; Ardhendu K Mandal; Nirmalendu Das (PLoS ONE, 2013)
Cerebral stroke is the leading cause of death and permanent disability among elderly people. In both humans and animals, cerebral ischemia damages the nerve cells in vulnerable regions of the brain, viz., hippocampus, cerebral cortex, cerebellum, and hypothalamus. The present study was conducted to evaluate the therapeutic efficacy of nanoencapsulated quercetin (QC) in combating ischemia-reperfusion-induced neuronal damage in young and aged Swiss Albino rats. Cerebral ischemia was induced by occlusion of the common carotid arteries of both young and aged rats followed by reperfusion. Nanoencapsulated quercetin (2.7 mg/kg b wt) was administered to both groups of animals via oral gavage two hours prior to ischemic insults as well as post-operation till day 3. Cerebral ischemia and 30 min consecutive reperfusion caused a substantial increase in lipid peroxidation, decreased antioxidant enzyme activities and tissue osmolality in different brain regions of both groups of animals. It also decreased mitochondrial membrane microviscosity and increased reactive oxygen species (ROS) generation in different brain regions of young and aged rats. Among the brain regions studied, the hippocampus appeared to be the worst affected region showing increased upregulation of iNOS and caspase-3 activity with decreased neuronal count in the CA1 and CA3 subfields of both young and aged rats. Furthermore, three days of continuous reperfusion after ischemia caused massive damage to neuronal cells. However, it was observed that oral treatment of nanoencapsulated quercetin (2.7 mg/kg b wt) resulted in downregulation of iNOS and caspase-3 activities and improved neuronal count in the hippocampal subfields even 3 days after reperfusion. Moreover, the nanoformulation imparted a significant level of protection in the antioxidant status in different brain regions, thus contributing to a better understanding of the given pathophysiological processes causing ischemic neuronal damage.